The Reflection of Apartheidic Trauma / Traumatic Apartheid in None to Accompany Me by Nadine Gordimer - KIZILTAŞ, Şahin (European Journal of Multidisciplinary Studies, 2017)
The world has gone through a trauma for centuries. Almost all nations have experienced all sorts of traumatic events and feelings in this period. Among those nations, the black seem to be the most unlucky and ill-fated suffered from traumatic disasters. However, among those black nations, the natives of South Africa have been the most piteous and wretched ones. Their misfortune began in 1652 with the arrival of white colonists in the country. Since then, the oppression and persecution of white European colonists and settlers on natives increasingly continued. Those native people were displaced from the lands inherited from their ancestors a few centuries ago. They were not allowed to have equal rights with white people and to share same environment in public premises. The natives have put up resistance against the racial and colonial practices of white settlers which excluded them from all living spaces; yet, they could not manage, even they came into power in 1994. Today their exclusion and violence victimization still go on and they are still subjected to inferior treatment by (post)colonial dominant white powers. As a white intellectual and writer who had European origins, Nadine Gordimer witnessed the repression and torturing of European settlers on native people in South Africa. In her novels, she has reflected the racial discrimination practiced by white people who have considered of themselves in a superior position compared to the black. This study aims to focus on how Gordimer has reflected the trauma which the black people of South Africa have experienced as a consequence of racist practices. This will contribute to clarify and get across the real and true-life traumatic narratives of native people in the colonized countries.
Keywords: The Reflection of Apartheidic Trauma / Traumatic Apartheid in None to Accompany Me by Nadine Gordimer